Neonatal Therapeutics: Considerations for Dosing - Zimmerman, Kanecia O.; Benjamin, Daniel K.; Becker, Mara L. (American Journal of Perinatology, 2019)
Neonates are a uniquely vulnerable population, compromised by immature physiology and critical illness if born premature. Furthermore, neonates have frequent exposures to drugs that lack adequate data on safety, efficacy, and appropriate dosing in this population. Key physiologic differences between neonates and older children and adults affect drug absorption, distribution, metabolism, and elimination. Adequate understanding and consideration of these differences is essential to ensure optimal dosing of therapeutic agents in this vulnerable population. Moreover, direct study of neonates through appropriately designed pharmacokinetic and pharmacodynamic studies can ensure the development of safe and effective therapeutics in our youngest populations of patients.
Keywords: neonate; premature; pharmacokinetics; pharmacodynamic; drugs; absorption; distribution; metabolism; elimination; meropenem; acyclovir; physiology